Effect of convergence to International Financial Reporting Standards on Companies Listed in the Colombian Stock Exchange (2019)
The purpose of this document is to analyze the effect of adopting International Financial Reporting Standards (IFRS), which must be compulsorily complied with as of 2015, on companies listed on the Colombian Stock Exchange (BVC by its acronym in Spanish). For this purpose, two samples were used, the first one with 52 Colombian companies on whose financial indicators such as ROE, OPM and ROIC obtained from the accounting information the mean difference was applied; these correspond to the year 2014 before and after the IFRS. In the second sample with 32 companies, their level of leverage, ordinary income, operating income, and profit and loss for year were analyzed to determine the effects of these variables on their market capitalization, using the difference in differences method, taking 2014 as the control year without IFRS and 2015 as the year of treatment with IFRS. The findings show that, in the 52 companies, adopting the standards did not signal changes in financial indicators before and after IFRS, as does the stock market value in the sample of 32 companies.